STUDY ON PHOTODEGRADATION ACTIVITY OF RHODAMINE B BY WO3/TIO2/SIO2 COMPOSITES IN VARIOUS MATERIAL WEIGHT CONDITION - Adhaina, Karina; Hindryawati, Noor; Koesnarpadi, Soerja (JURNAL ATOMIK, 2020)
A study on photodegradation activity of Rhodamine B by WO3/TiO2/SiO2 composites in various material weight condition has been conducted. The photocatalytic process was carried out in a closed reactor equipped with visible lamps (grow LED 10 watt). To identify crystal structure, morphology and composition of composite WO3/TiO2/SiO2, the characterization performed using Scanning Electron Microscopy-Energy Diffraction-X (SEM-EDX). The results of characterization using SEM-EDX showed that composites have a non-uniform pore morphology. The photocatalytic test showed the optimum material weight at 0.15 gram with percent degradation of Rhodamine B dyes of 85.10%.